2021
DOI: 10.3390/foods10092110
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Acrylamide in Selected Foods from the Romanian Market

Abstract: Several processed food products may contain toxic compounds considered risk factors for human health. Known for its possible carcinogenic effects, acrylamide is an organic compound periodically analyzed by the entities responsible for consumer safety. Knowing the acrylamide content of food offers the possibility of implementing corrective measures when needed, targeted at lowering its level. The aim of the paper was to screen for the presence of acrylamide in four products consumed almost daily in Romania and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Studies demonstrated that raw foods are free of acrylamide, whereas processed foods at temperatures above 120 °C or higher contain varying proportions (concentrations) of acrylamide depending on the processing temperature and time. The amount of acrylamide content is different from product to product [ 42 ]. The severe heat treatments during roasting and the high starch content of barley could be favorable conditions for the formation of acrylamide in Kolo, similar to the observation of [ 38 ] for roasted barley that was used in production of Keribo.…”
Section: Safety Of Kolomentioning
confidence: 99%
“…Studies demonstrated that raw foods are free of acrylamide, whereas processed foods at temperatures above 120 °C or higher contain varying proportions (concentrations) of acrylamide depending on the processing temperature and time. The amount of acrylamide content is different from product to product [ 42 ]. The severe heat treatments during roasting and the high starch content of barley could be favorable conditions for the formation of acrylamide in Kolo, similar to the observation of [ 38 ] for roasted barley that was used in production of Keribo.…”
Section: Safety Of Kolomentioning
confidence: 99%
“…Researchers have shown that processed foods at 120 °C or higher contain different amounts (concentrations) of acrylamide depending on the processing temperature and duration, whereas raw foods are free of acrylamide. Each product has a variable concentration of acrylamide [ 7 ] based on its amino acid and sugar content. The high starch content of barley and the intense heat treatments used during roasting may have created ideal circumstances for the production of acrylamide in Kolo, comparable to the findings of [ 4 ] for roasted barley that was used in production of Keribo.…”
Section: Traditional Food Types and Acrylamide Formationmentioning
confidence: 99%
“…Acrylamide is a toxic chemical compound that can be found in various foods, such as deep-fried, roasted, and baked products that are exposed to high temperatures [ 3 , 4 ]. Its presence in these foods has attracted significant attention from both consumers and researchers due to its potential health implications [ [5] , [6] , [7] ]. Acrylamide is a known carcinogen and has been linked to an increased risk of several types of cancer, including lung cancer, prostate cancer [ 8 ], and breast cancer [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A vinyl-substituted primary amide, it is produced industrially, chiefly as a precursor to polyacrylamides, with the latter being used as watersoluble thickeners and flocculation agents mainly for industrial processes. However, acrylamide also forms naturally in the burnt areas of starchy foods, that is, as a result of high-temperature cooking (i.e., frying, roasting, and baking) [1,2], being found in such products as potatoes [3,4], bread [4,5], and coffee [4], as well as in cosmetic products [6]. While there has been intensive investigation into the presence of acrylamide in numerous food samples, this has not been the case concerning biological samples [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Chromatographic separation has been reported to be achieved with typical reversed phase analytical columns C18 [4,6], graphitized carbon columns [7], and a hydrophilic interaction chromatography column (HILIC) [5].…”
Section: Introductionmentioning
confidence: 99%